AN IMPROVING STUDENTS LISTENING SKILL THROUGH INTERACTIVE MULTIMEDIA AT XI GRADE OF SMK NEGERI 1 BANGKINANG KOTA - Putri Asilestari (Universitas Pahlawan Tuanku Tambusai, 2016)
Learning method inovation will influence learning media used and it is hoped to improve learning qualities. This research was done to know the students activities in learning critical listening by using interactive multimedia and to measure the effetiveness of that multimedia in improving students listening skill. The data was taken through test, observation, and interview. The result of the research were (1) the students created active, creative, and effective learning process independenly in measuring and developing each step of listening learning model. (2) Interactive multimedia was effective learning media to improve students listening skill. It could be seen from improving listening skill in limited test at experiment class was 42,98%, whereas at control class the rise was only 7,36%. For extensive test, the improving of listening skill at experiment class was 33,88%, while control class was only up at 2,62%. . (3) Learning media with interactive multimedia can improve students listening skill than audio learning media because listening is not only aural aspet but also visual aspect integrated with multimedia.